Enhanced Defluoridation Capacity From Aqueous Media via Hydroxyapatite Decorated With Carbon Nanotube - Tang, Qingzi; Duan, Tongdan; Li, Peng; Zhang, Ping; Wu, Daishe (Frontiers in Chemistry, 2018)
In this work, the potential of a novel carbon nanotube-doped hydroxyapatite composite (CNT-HAP) for fluoride removal was investigated. The synthesized CNT-HAP composite was systematically characterized by X-ray diffraction(XRD), Fourier Transform infrared spectroscopy(FTIR), scanning electron microscope (SEM) and Brunauer–Emmett–Teller(BET). Batch adsorption experiments were conducted to investigate the defluorination capacity of CNT-HAP. The CNT-HAP composite has a maximum adsorption capacity of 11.05 mg·g-1 for fluoride, and the isothermal adsorption data were fitted by the Freundlich model to calculate the thermodynamic parameters. Thermodynamic analysis implies that the adsorption of fluoride on CNT-HAP is a spontaneous process. Furthermore, the adsorption of fluoride follows pseudo-second-order model. The effects of solution pH, co-existing anions and reaction temperature on defluorination efficiency were examined to optimize the operation conditions for fluoride adsorption. It is found that the optimized pH value for fluoride removal by CNT-HAP composite is 6. In addition, among five common anions studied in this work, the presence of HCO3- and PO43- could considerably affect the fluoride removal by CNT-HPA in aqueous media. Finally, the underlying mechanism for the fluoride removal by CNT-HAP is analysed, and an anion exchange process is proposed.